2014
DOI: 10.1159/000356643
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Organic Anion Transporter Expression Is a Risk Factor for Hepatocellular Carcinoma in Chronic Hepatitis C Patients: A Propensity Score Matching Study

Abstract: Objectives: Recent reports indicated that reduced SLC22A7 (a gene-encoding organic anion transporter 2) expression in noncancerous liver tissue predicts hepatocellular carcinoma (HCC) recurrence after curative resection. Our study aimed to elucidate the association between SLC22A7 expression and HCC development in chronic hepatitis C patients. Methods: HCC recurrence after local ablation therapy and SLC22A7 expression in noncancerous liver tissue were analyzed in 20 patients. Subsequently, the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…In contrast, some other genes were shown to be down-regulated in HCC or have anti-tumor effects during HCC development. Several solute carrier family 22 members including SLC22A1, SLC22A3, and SLC22A7 were shown to be under-expressed in HCC and their down-regulation was associated with the poor prognosis of HCC patients (Heise et al, 2012; Schaeffeler et al, 2011; Yasui et al, 2014). CD5 molecule-like (CD5L), also named inhibitor of microphage (AIM), was reported to have potent preventive effect on HCC (Maehara et al, 2014; Ozawa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some other genes were shown to be down-regulated in HCC or have anti-tumor effects during HCC development. Several solute carrier family 22 members including SLC22A1, SLC22A3, and SLC22A7 were shown to be under-expressed in HCC and their down-regulation was associated with the poor prognosis of HCC patients (Heise et al, 2012; Schaeffeler et al, 2011; Yasui et al, 2014). CD5 molecule-like (CD5L), also named inhibitor of microphage (AIM), was reported to have potent preventive effect on HCC (Maehara et al, 2014; Ozawa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that ALF did not alter urinary excretion of AZT or its metabolite, GAZT, thus suggesting that the functions of OAT1 and OAT3 in renal proximal tubule cells may not be changed by ALF. Decreased hepatic OAT2 activity and expression may also contribute to the higher oral exposure of AZT in ALF rats observed in this study, as evidenced by the decrease in liver OAT2 expression found in chronic hepatitis C patients [65] .…”
Section: Discussionmentioning
confidence: 55%
“… 6–9 In humans, hepatitis is related to viral infection, leading to a chronic lesion and later fibrosis. 9 As hepatic fibrosis progresses, hepatocytes with reduced function or dysfunction display impaired Gd-EOB-DTPA uptake mediated via OATP. 24 Therefore, liver enhancement in the hepatocyte phase is reduced.…”
Section: Discussionmentioning
confidence: 99%